Cell‐in‐Catalytic‐Shell Nanoarchitectonics: Catalytic Empowerment of Individual Living Cells by Single‐Cell Nanoencapsulation. Issue 30 (19th June 2022) - Lee, Hojae; Park, Joohyouck; Kim, Nayoung; Youn, Wongu; Yun, Gyeongwon; Han, Sang Yeong; Nguyen, Duc Tai; Choi, Insung S.
Abstract: Cell‐in‐shell biohybrid structures, synthesized by encapsulating individual living cells with exogenous materials, have emerged as exciting functional entities for engineered living materials, with emergent properties outside the scope of biochemical modifications. Artificial exoskeletons have, to date, provided physicochemical shelters to the cells inside in the first stage of technological development, and further advances in the field demand catalytically empowered, cellular hybrid systems that augment the biological functions of cells and even introduce completely new functions to the cells. This work describes a facile and generalizable strategy for empowering living cells with extrinsic catalytic capability through nanoencapsulation of living cells with a supramolecular metal–organic complex of Fe 3+ and benzene‐1, 3, 5‐tricarboxylic acid (BTC). A series of enzymes are embedded in situ, without loss of catalytic activity, in the Fe 3+ ‐BTC shells, not to mention the superior characteristics of cytocompatible and rapid shell‐forming processes. The nanoshell enhances the catalytic efficiency of multienzymatic cascade reactions by confining reaction intermediates to its internal voids and the nanoencapsulated cells acquire exogenous biochemical functions, including enzymatic cleavage of lethal octyl‐β‐d ‐glucopyranoside into d ‐glucose, with autonomous cytoprotection. The system will provide a versatile, nanoarchitectonic tool for interfacing biological cells with functional materials, especially for catalytic bioempowerment of living cells. Abstract : Cell‐in‐catalytic‐shell biohybrid structures are constructed by in situ supramolecular self‐assembly of Fe 3+ and benzene‐1, 3, 5‐tricarboxylic acid, with concomitant enzyme embedment. The Fe 3+ ‐BTC nanoshells on individual living cells enhance the catalytic efficiency of multienzymatic cascade reactions by confining the reaction intermediates to the internal voids and impart extrinsic functions to the cells beyond the scope of biological evolution.